Controllable release type organic solid acid preparation method

By preparing pH and temperature dual-sensitivity polymer carriers and modified nanosilicon dioxide, controllable release organic solid acid composite microspheres are prepared, which solves the problems of inaccurate acid release and uneven acid corrosion in the existing acidification treatment technology, and realizes multiple response control and multi-stage release of acids, which significantly improves the effect and stability of acid treatment.

CN119552647APending Publication Date: 2025-03-04KARAMAY CHENGUANG CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411765443.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing acidification treatment technology has problems such as the strong corrosiveness of the acid solution and the fast reaction speed, which makes it difficult to penetrate deep into the reservoir, and the uneven reaction of the acid rock to form wormholes, and it is difficult to achieve precise control of the acid release process.

Method used

Using the preparation method of controlled-release organic solid acid, the pH and temperature dual-sensitivity polymer support is prepared, the acid precursor is loaded onto the polymer support, and the nanosilicon dioxide is surface modified. The composite microspheres are prepared by spray drying to achieve multiple response control and multi-stage release of the acid.

Benefits of technology

Accurate control of the acid release process is achieved, the effective time of acid action is extended, the stability of the acid agent under high temperature and high pressure conditions is improved, the uniformity of acid corrosion is improved, the wormhole effect is avoided, and the negative impact on the environment and equipment is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005168818830000131
    Figure BDA0005168818830000131
  • Figure BDA0005168818830000141
    Figure BDA0005168818830000141
  • Figure BDA0005168818830000142
    Figure BDA0005168818830000142
Patent Text Reader

Abstract

The invention relates to the technical field of organic solid acids, in particular to a preparation method of a controllable release type organic solid acid, which comprises the following steps: (1) preparing a pH and temperature dual-sensitive polymer carrier; (2) loading an acid precursor onto the polymer support; (3) carrying out surface modification on the nano silicon dioxide; and (4) mixing the polymer loaded with the acid precursor with the modified nano silicon dioxide, and preparing the composite microspheres by adopting a spray drying method. The pH-sensitive polymer PDEAEMA and the temperature-sensitive polymer PNIPAM are combined, so that the dual response to the pH and temperature of the reservoir is realized. A tertiary amine group in a PDEAEMA molecule is protonated in a low-pH environment, so that a polymer chain is stretched, and release of an acid precursor is promoted. Meanwhile, the PNIPAM is subjected to phase change when the LCST is higher than the LCST (about 32 DEG C) of the PNIPAM, the hydrophilic property is converted into the hydrophobic property, a polymer network is shrunk, and accurate control over acid release is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of organic solid acids, and in particular to a method for preparing a controllable-release organic solid acid. Background Art

[0002] In the field of oil and gas development, acidizing is a commonly used reservoir transformation technology that aims to increase the permeability near the wellbore, thereby increasing oil and gas production. Traditional acidizing mainly uses inorganic acids or organic acids such as hydrochloric acid and hydrofluoric acid. However, these methods have many problems, such as the strong corrosiveness of the acid, the fast reaction speed that makes it difficult for the acid to penetrate the reservoir, and the uneven acid-rock reaction to form wormholes. To solve these problems, the industry has developed various slow-release acid systems, such as emulsified acid and gel acid. However, these systems still find it difficult to achieve precise control of the acid release process, especially under complex reservoir conditions.

[0003] The closest existing technology is a coated solid acid, which encapsulates the acid precursor in a polymer and controls the release of the acid by polymer degradation. However, this method has poor responsiveness to changes in reservoir environment and is difficult to adapt to the diverse needs of different reservoirs. In addition, the existing technology also has problems such as a single acid release rate, short duration, and insufficient mechanical strength, which limits its application in deep and high-temperature and high-pressure reservoirs.

[0004] Based on the above background, it is particularly necessary to develop a new acidizing system that can accurately control acid release, adapt to complex reservoir conditions, and have a long-lasting effect. Summary of the invention

[0005] The present invention aims to solve the following technical problems: The present invention aims to solve the following technical problems: How to achieve multi-response control of the acid release process? How to extend the effective action time of the acid to achieve deep acidification? How to improve the stability of the acidifier under high temperature and high pressure conditions? How to improve the uniformity of acid etching and avoid the wormhole effect? ​​How to reduce the negative impact of acidification treatment on the environment and equipment?

[0006] The object of the present invention is to provide a method for preparing a controlled-release organic solid acid, comprising the following steps:

[0007] (1) Preparing a pH and temperature dual-sensitive polymer carrier;

[0008] (2) loading the acid precursor onto the polymer carrier;

[0009] (3) Surface modification of nano-silicon dioxide;

[0010] (4) The polymer loaded with the acid precursor is mixed with the modified nano-silica, and the composite microspheres are prepared by a spray drying method.

[0011] Preferably, the raw material components and their contents used in the method are:

[0012] 60-80 parts by weight of acid precursor;

[0013] 15-25 parts by weight of pH sensitive polymer;

[0014] 5-10 parts by weight of temperature-sensitive polymer;

[0015] 1-3 parts by weight of a cross-linking agent;

[0016] 0.5-1.5 parts by weight of surfactant;

[0017] Initiator 0.1-0.5 parts by weight;

[0018] 2-5 parts by weight of nano silicon dioxide.

[0019] Preferably, the acid precursor is 2-acetoxypropionic acid; the pH sensitive polymer is poly (N,N-dimethylaminoethyl methacrylate) (PDEAEMA); and the temperature sensitive polymer is poly (N-isopropylacrylamide) (PNIPAM).

[0020] Preferably, the cross-linking agent is N,N'-methylenebisacrylamide; the surfactant is Tween 80; and the initiator is ammonium persulfate.

[0021] Preferably, step (1) comprises the following sub-steps:

[0022] First, add deionized water into a four-necked flask and pass nitrogen gas to remove oxygen;

[0023] Secondly, dissolving the pH-sensitive polymer monomer, the temperature-sensitive polymer monomer and the cross-linking agent in anhydrous ethanol and stirring evenly;

[0024] Then, the monomer solution was slowly added dropwise to deionized water, and the stirring speed and temperature were controlled;

[0025] Again, the initiator was added, the temperature was raised to 70°C, and the reaction was carried out for 4 hours under nitrogen protection;

[0026] Finally, the reaction solution was cooled to room temperature, dialyzed for 48 hours, and freeze-dried to obtain a pH and temperature dual-sensitive polymer carrier.

[0027] Preferably, step (2) comprises the following sub-steps:

[0028] First, the acid precursor was dissolved in anhydrous ethanol;

[0029] Secondly, the polymer carrier is dispersed in deionized water;

[0030] Then, the acid precursor solution was slowly added dropwise to the polymer carrier dispersion and stirred at room temperature for 2 hours;

[0031] Finally, the surfactant was added and stirring was continued for 30 minutes.

[0032] Preferably, step (3) comprises the following sub-steps:

[0033] First, nano-silica was dispersed in anhydrous toluene and ultrasonicated for 30 min;

[0034] Secondly, (3-aminopropyl)triethoxysilane APTES was added and refluxed at 60 °C for 6 hours;

[0035] Finally, the product was centrifuged, washed with anhydrous ethanol three times, and dried in vacuum at 80 °C for 12 h.

[0036] Preferably, the process parameters of spray drying in step (4) are:

[0037] Feed rate 5-10mL / min, inlet temperature 140-160℃, outlet temperature 60-80℃, atomization pressure 0.2-0.3MPa.

[0038] Preferably, the average particle size of the nano-silicon dioxide is 50-100 nm.

[0039] Preferably, the composite microspheres prepared in step (4) are vacuum dried at 60° C. for 24 hours.

[0040] The present invention proposes a method for preparing a controlled-release organic solid acid through ingenious design and optimization, which has the following innovative features and beneficial effects:

[0041] 1. Multiple response mechanisms: The present invention combines the pH-sensitive polymer PDEAEMA and the temperature-sensitive polymer PNIPAM to achieve dual response to reservoir pH and temperature. The tertiary amine groups in the PDEAEMA molecule are protonated in a low pH environment, causing the polymer chain to stretch and promote the release of acid precursors. At the same time, PNIPAM undergoes a phase transition above its LCST (about 32°C), changing from hydrophilic to hydrophobic, shrinking the polymer network. The synergistic effect of these two mechanisms creates a unique "squeeze-release" effect, achieving precise control of acid release.

[0042] 2. Multi-stage release control: By introducing surface-modified nano-silica, the present invention constructs a multi-stage release system. Nano-silica not only provides physical barrier, but also forms reversible hydrogen bonds with acid precursors through its surface amino groups, further regulating the release kinetics. This multi-stage control mechanism significantly prolongs the effective action time of the acid, which is conducive to achieving deep acidification.

[0043] 3. Enhanced structural stability: The present invention uses N,N'-methylenebisacrylamide as a crosslinking agent to form a three-dimensional network structure, which greatly improves the mechanical strength and thermal stability of the polymer carrier. Unexpectedly, the introduction of nano-silica not only regulates the release behavior, but also further enhances the structural stability of the composite microspheres, allowing them to remain intact under high temperature and high pressure environments.

[0044] 4. Adaptive release kinetics: Thanks to the multiple response mechanisms and multi-level release control, the composite microspheres of the present invention exhibit excellent adaptability. Under different pH and temperature conditions, the microspheres can automatically adjust the acid release rate to ensure the best acidification effect under various reservoir conditions.

[0045] 5. Improved acid etching uniformity: By controlling the slow and uniform release of acid, the present invention significantly improves the uniformity of the acid etching channel. This effect is due to the uniform distribution and continuous release of the composite microspheres in the reservoir, which effectively avoids the wormhole effect in traditional acidizing and improves the effectiveness and efficiency of the acidizing treatment.

[0046] 6. Environmental friendliness: The present invention uses 2-acetoxypropionic acid as an acid precursor, and its hydrolysis process is mild, which greatly reduces the risk of corrosion to ground equipment and wellbore. At the same time, since the acid is encapsulated in microspheres, the environmental risk of waste acid treatment is reduced and the operation safety is improved.

[0047] 7. Synergistic effect: The components of the present invention exhibit unexpected synergistic effects. For example, the combination of PDEAEMA and PNIPAM not only achieves dual response to pH and temperature, but also enhances sensitivity to environmental changes through interaction. Nano-silica not only regulates release kinetics, but also improves the mechanical properties of the composite microspheres.

[0048] In summary, the present invention successfully solves many problems faced by traditional acidizing treatment through multiple response mechanisms, multi-stage release control and material optimization. Its excellent controlled release performance, long-lasting effect, high stability and environmentally friendly characteristics provide a new technical path for acidizing treatment under complex reservoir conditions, which is expected to significantly increase oil and gas recovery while reducing environmental risks. This innovative acidizing system not only promotes the advancement of reservoir transformation technology, but also provides new possibilities for sustainable oil and gas development. DETAILED DESCRIPTION

[0049] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0050] Example 1: A method for preparing a controlled-release organic solid acid

[0051] This embodiment provides a method for preparing a controlled-release organic solid acid, the method comprising the following steps:

[0052] (1) Preparation of pH and temperature dual-sensitive polymer carriers:

[0053] First, add 200 mL of deionized water to a 500 mL four-necked flask and pass nitrogen for 15 minutes to deoxygenate. Secondly, dissolve 15 parts by weight of poly(N,N-dimethylaminoethyl methacrylate) (PDEAEMA) monomer, 5 parts by weight of poly(N-isopropylacrylamide) (PNIPAM) monomer and 1 part by weight of N,N'-methylenebisacrylamide in 50 mL of anhydrous ethanol and stir evenly. Then, slowly add the monomer solution dropwise to deionized water at a stirring speed of 300 rpm and keep the temperature at 25 °C. Again, add 0.1 parts by weight of ammonium persulfate, heat to 70 °C, and react for 4 hours under nitrogen protection. Finally, cool the reaction solution to room temperature, dialyze for 48 hours to remove unreacted monomers and small molecule impurities, and freeze-dry to obtain a pH and temperature dual-sensitive polymer carrier.

[0054] (2) Loading of acid precursor:

[0055] First, 60 parts by weight of 2-acetoxypropionic acid were dissolved in 100 mL of absolute ethanol. Secondly, the polymer carrier was dispersed in 200 mL of deionized water at a stirring speed of 500 rpm. Then, the acid precursor solution was slowly added dropwise to the polymer carrier dispersion and stirred at room temperature for 2 hours. Finally, 0.5 parts by weight of Tween 80 was added and stirring was continued for 30 minutes.

[0056] (3) Surface modification of nano-silicon dioxide:

[0057] First, 2 parts by weight of nano-silica with an average particle size of 50 nm was dispersed in 100 mL of anhydrous toluene and ultrasonicated for 30 minutes. Then, 3 mL of (3-aminopropyl) triethoxysilane (APTES) was added and refluxed at 60°C for 6 hours. Finally, the mixture was centrifuged, washed with anhydrous ethanol three times, and vacuum dried at 80°C for 12 hours.

[0058] (4) Preparation of composite microspheres:

[0059] First, the polymer dispersion loaded with acid precursor was mixed with modified nano-silica, stirred at 800 rpm for 2 hours at room temperature. Secondly, composite microspheres were prepared by spray drying. The feed rate was 5 mL / min, the inlet temperature was 140 ° C, the outlet temperature was 60 ° C, and the atomization pressure was 0.2 MPa. Finally, the product was collected and vacuum dried at 60 ° C for 24 hours.

[0060] Preferably, in the embodiment of the present invention, PDEAEMA, as a pH-sensitive carrier, can swell in a low pH environment to promote the release of acid precursors. At the same time, PNIPAM, as a temperature-sensitive carrier, can automatically adjust the release rate according to the reservoir temperature. This dual response mechanism can achieve precise control of acid release, thereby improving the effect of acidification treatment.

[0061] Example 2: A method for preparing a controlled-release organic solid acid

[0062] This embodiment provides another method for preparing a controlled-release organic solid acid, which comprises the following steps:

[0063] (1) Preparation of pH and temperature dual-sensitive polymer carriers:

[0064] First, add 200 mL of deionized water to a 500 mL four-necked flask and pass nitrogen for 15 minutes to deoxygenate. Secondly, dissolve 25 parts by weight of PDEAEMA monomer, 10 parts by weight of PNIPAM monomer and 3 parts by weight of N,N'-methylenebisacrylamide in 50 mL of anhydrous ethanol and stir evenly. Then, slowly add the monomer solution dropwise to the deionized water at a stirring speed of 300 rpm and keep the temperature at 25 ° C. Again, add 0.5 parts by weight of ammonium persulfate, heat to 70 ° C, and react for 4 hours under nitrogen protection. Finally, the reaction solution was cooled to room temperature, dialyzed for 48 hours, and freeze-dried to obtain a pH and temperature dual-sensitive polymer carrier.

[0065] (2) Loading of acid precursor:

[0066] First, 80 parts by weight of 2-acetoxypropionic acid were dissolved in 100 mL of absolute ethanol. Secondly, the polymer carrier was dispersed in 200 mL of deionized water at a stirring speed of 500 rpm. Then, the acid precursor solution was slowly added dropwise to the polymer carrier dispersion and stirred at room temperature for 2 hours. Finally, 1.5 parts by weight of Tween 80 were added and stirring was continued for 30 minutes.

[0067] (3) Surface modification of nano-silicon dioxide:

[0068] First, 5 parts by weight of nano-silica with an average particle size of 100 nm was dispersed in 100 mL of anhydrous toluene and ultrasonicated for 30 minutes. Then, 5 mL of APTES was added and refluxed at 60°C for 6 hours. Finally, the mixture was centrifuged, washed with anhydrous ethanol for 3 times, and vacuum dried at 80°C for 12 hours.

[0069] (4) Preparation of composite microspheres:

[0070] First, the polymer dispersion loaded with acid precursor was mixed with modified nano-silica, stirred at 800 rpm for 2 hours at room temperature. Secondly, composite microspheres were prepared by spray drying. The feed rate was 10 mL / min, the inlet temperature was 160 ° C, the outlet temperature was 80 ° C, and the atomization pressure was 0.3 MPa. Finally, the product was collected and vacuum dried at 60 ° C for 24 hours.

[0071] Further, in the present embodiment, the dosage of PDEAEMA and PNIPAM is increased, which can improve the responsiveness and loading capacity of the polymer carrier. At the same time, the content of the acid precursor is increased, which can improve the effect of the acidification treatment. The increase in the nano-silica particle size can further delay the release rate of the acid and achieve a longer continuous acidification.

[0072] Example 3: A method for preparing a controlled release organic solid acid

[0073] This embodiment provides a third method for preparing a controlled-release organic solid acid, which comprises the following steps:

[0074] (1) Preparation of pH and temperature dual-sensitive polymer carriers:

[0075] First, add 200 mL of deionized water to a 500 mL four-necked flask and pass nitrogen for 15 minutes to deoxygenate. Secondly, dissolve 20 parts by weight of PDEAEMA monomer, 7.5 parts by weight of PNIPAM monomer and 2 parts by weight of N,N'-methylenebisacrylamide in 50 mL of anhydrous ethanol and stir evenly. Then, slowly add the monomer solution dropwise to the deionized water at a stirring speed of 300 rpm and keep the temperature at 25 ° C. Again, add 0.3 parts by weight of ammonium persulfate, heat to 70 ° C, and react for 4 hours under nitrogen protection. Finally, the reaction solution was cooled to room temperature, dialyzed for 48 hours, and freeze-dried to obtain a pH and temperature dual-sensitive polymer carrier.

[0076] (2) Loading of acid precursor:

[0077] First, 70 parts by weight of 2-acetoxypropionic acid were dissolved in 100 mL of absolute ethanol. Secondly, the polymer carrier was dispersed in 200 mL of deionized water at a stirring speed of 500 rpm. Then, the acid precursor solution was slowly added dropwise to the polymer carrier dispersion and stirred at room temperature for 2 hours. Finally, 1 part by weight of Tween 80 was added and stirring was continued for 30 minutes.

[0078] (3) Surface modification of nano-silicon dioxide:

[0079] First, 3.5 parts by weight of nano-silica with an average particle size of 75 nm was dispersed in 100 mL of anhydrous toluene and ultrasonicated for 30 minutes. Then, 4 mL of APTES was added and refluxed at 60°C for 6 hours. Finally, the mixture was centrifuged, washed with anhydrous ethanol three times, and vacuum dried at 80°C for 12 hours.

[0080] (4) Preparation of composite microspheres:

[0081] First, the polymer dispersion loaded with acid precursor was mixed with modified nano-silica, stirred at 800 rpm for 2 hours at room temperature. Second, composite microspheres were prepared by spray drying. The feed rate was 7.5 mL / min, the inlet temperature was 150 ° C, the outlet temperature was 70 ° C, and the atomization pressure was 0.25 MPa. Finally, the product was collected and vacuum dried at 60 ° C for 24 hours.

[0082] Among them, this embodiment adopts intermediate component ratio and preparation parameters to achieve a balance of performance. This formula can provide a moderate acid release rate and duration while maintaining good pH and temperature responsiveness, and is suitable for a variety of reservoir conditions.

[0083] Example 4: A method for preparing a controlled release organic solid acid

[0084] This embodiment provides a fourth method for preparing a controlled-release organic solid acid, which comprises the following steps:

[0085] (1) Preparation of pH and temperature dual-sensitive polymer carriers:

[0086] First, add 200 mL of deionized water to a 500 mL four-necked flask and pass nitrogen for 15 minutes to deoxygenate. Secondly, dissolve 22 parts by weight of PDEAEMA monomer, 8 parts by weight of PNIPAM monomer and 2.5 parts by weight of N,N'-methylenebisacrylamide in 50 mL of anhydrous ethanol and stir evenly. Then, slowly add the monomer solution dropwise to the deionized water at a stirring speed of 300 rpm and keep the temperature at 25 ° C. Again, add 0.4 parts by weight of ammonium persulfate, heat to 70 ° C, and react for 4 hours under nitrogen protection. Finally, the reaction solution was cooled to room temperature, dialyzed for 48 hours, and freeze-dried to obtain a pH and temperature dual-sensitive polymer carrier.

[0087] (2) Loading of acid precursor:

[0088] First, 75 parts by weight of 2-acetoxypropionic acid were dissolved in 100 mL of anhydrous ethanol. Secondly, the polymer carrier was dispersed in 200 mL of deionized water at a stirring speed of 500 rpm. Then, the acid precursor solution was slowly added dropwise to the polymer carrier dispersion and stirred at room temperature for 2 hours. Finally, 1.2 parts by weight of Tween 80 were added and stirring was continued for 30 minutes.

[0089] (3) Surface modification of nano-silicon dioxide:

[0090] First, 4 parts by weight of nano-silica with an average particle size of 85 nm was dispersed in 100 mL of anhydrous toluene and ultrasonicated for 30 minutes. Then, 4.5 mL of APTES was added and refluxed at 60°C for 6 hours. Finally, the mixture was centrifuged, washed with anhydrous ethanol three times, and vacuum dried at 80°C for 12 hours.

[0091] (4) Preparation of composite microspheres:

[0092] First, the polymer dispersion loaded with acid precursor was mixed with modified nano-silica, stirred at 800 rpm for 2 hours at room temperature. Secondly, composite microspheres were prepared by spray drying. The feed rate was 8.5 mL / min, the inlet temperature was 155 ° C, the outlet temperature was 75 ° C, and the atomization pressure was 0.28 MPa. Finally, the product was collected and vacuum dried at 60 ° C for 24 hours.

[0093] It is worth noting that this embodiment aims to optimize performance by adjusting the proportion of each component and the preparation parameters. The increased PDEAEMA content can improve pH responsiveness, while the appropriate PNIPAM content ensures good temperature responsiveness. At the same time, by adjusting the particle size and content of nano-silica, the acid release curve can be further optimized to achieve more precise control. This optimized formula can adapt to a wider range of reservoir conditions and improve the applicability and effect of acidizing treatment.

[0094] This multi-response, multi-stage release design can not only improve the effect of acidizing treatment, but also reduce damage to the reservoir, providing a new technical option for oil and gas development under complex reservoir conditions.

[0095] Comparative Example 1: Preparation method of a single pH-sensitive polymer carrier

[0096] This comparative example is intended to verify the importance of the temperature-sensitive polymer PNIPAM and is compared with Example 1. The method comprises the following steps:

[0097] (1) Preparation of pH-sensitive polymer carriers:

[0098] First, add 200 mL of deionized water to a 500 mL four-necked flask and pass nitrogen for 15 minutes to deoxygenate. Secondly, dissolve 20 parts by weight of PDEAEMA monomer and 1 part by weight of N,N'-methylenebisacrylamide in 50 mL of anhydrous ethanol and stir evenly. Then, slowly add the monomer solution dropwise to the deionized water at a stirring speed of 300 rpm and keep the temperature at 25 °C. Again, add 0.1 parts by weight of ammonium persulfate, heat to 70 °C, and react for 4 hours under nitrogen protection. Finally, cool the reaction solution to room temperature, dialyze for 48 hours, and freeze-dry to obtain a pH-sensitive polymer carrier.

[0099] Steps (2) to (4) are the same as those in Example 1.

[0100] Preferably, in this comparative example, due to the lack of temperature-sensitive polymer PNIPAM, the prepared composite microspheres can only respond to pH changes and cannot automatically adjust the release rate according to the reservoir temperature. This may result in too fast a release rate of acid in a high-temperature reservoir, and it is impossible to achieve a sustained deep acidification effect.

[0101] Comparative Example 2: Preparation method without nano-silicon dioxide

[0102] This comparative example is intended to verify the importance of nano-silicon dioxide in the multi-stage release mechanism and is compared with Example 2. The method comprises the following steps:

[0103] Steps (1) and (2) are the same as in Example 2.

[0104] (3) Preparation of composite microspheres:

[0105] First, the polymer dispersion loaded with acid precursor was directly spray dried at a feed rate of 10 mL / min, an inlet temperature of 160°C, an outlet temperature of 80°C, and an atomization pressure of 0.3 MPa. Finally, the product was collected and vacuum dried at 60°C for 24 hours.

[0106] Furthermore, due to the lack of nano-silicon dioxide in this comparative example, a multi-stage release mechanism cannot be formed. Nano-silicon dioxide plays a role of physical barrier and adsorption-desorption in the present invention, and its absence may lead to too fast release of acid precursors and failure to achieve long-term acidification.

[0107] Comparative Example 3: Preparation method using traditional liquid acid

[0108] This comparative example is intended to verify the superiority of the solid acid precursor and is compared with Example 3. The method comprises the following steps:

[0109] (1) Preparation of pH and temperature dual-sensitive polymer carriers:

[0110] Same as Example 3.

[0111] (2) Liquid acid loading:

[0112] First, 70 parts by weight of hydrochloric acid (37% concentration) was diluted to 200 mL. Next, the polymer carrier was dispersed in the diluted hydrochloric acid solution and stirred at 500 rpm for 2 hours at room temperature. Finally, 1 part by weight of Tween 80 was added and stirring was continued for 30 minutes.

[0113] Steps (3) and (4) are the same as in Example 3.

[0114] Among them, the comparative example uses traditional liquid acid instead of solid acid precursor, which may reduce the safety of storage and transportation, and it is difficult to achieve slow release and deep acidification effect. This highlights the innovation and superiority of using solid acid precursor in the present invention.

[0115] Comparative Example 4: Preparation method without surfactant

[0116] This comparative example is intended to verify the important role of surfactant Tween 80 in improving dispersibility and stability, and is compared with Example 4. The method comprises the following steps:

[0117] Steps (1), (3) and (4) are the same as those in Example 4.

[0118] (2) Loading of acid precursor:

[0119] First, 75 parts by weight of 2-acetoxypropionic acid were dissolved in 100 mL of anhydrous ethanol. Next, the polymer carrier was dispersed in 200 mL of deionized water at a stirring speed of 500 rpm. Then, the acid precursor solution was slowly added dropwise to the polymer carrier dispersion and stirred at room temperature for 2 hours.

[0120] It is worth noting that the lack of surfactant Tween 80 in this comparative example may reduce the dispersibility of the acid precursor in the polymer carrier, thereby affecting the uniformity and stability of the composite microspheres. This may lead to uneven acid release and affect the effect of the acidification treatment.

[0121] Comparative Example 5: Preparation method of high-ratio temperature-sensitive polymer

[0122] This comparative example is intended to verify the importance of the ratio of pH-sensitive polymer to temperature-sensitive polymer, and is compared with Example 1. The method comprises the following steps:

[0123] (1) Preparation of pH and temperature dual-sensitive polymer carriers:

[0124] First, add 200 mL of deionized water to a 500 mL four-necked flask and pass nitrogen for 15 minutes to deoxygenate. Secondly, dissolve 5 parts by weight of PDEAEMA monomer, 15 parts by weight of PNIPAM monomer and 1 part by weight of N,N'-methylenebisacrylamide in 50 mL of anhydrous ethanol and stir evenly. Then, slowly add the monomer solution dropwise to the deionized water at a stirring speed of 300 rpm and keep the temperature at 25 ° C. Again, add 0.1 parts by weight of ammonium persulfate, heat to 70 ° C, and react for 4 hours under nitrogen protection. Finally, the reaction solution was cooled to room temperature, dialyzed for 48 hours, and freeze-dried to obtain a pH and temperature dual-sensitive polymer carrier.

[0125] Steps (2) to (4) are the same as those in Example 1.

[0126] Preferably, in this comparative example, due to the high proportion of PNIPAM, the responsiveness of the composite microspheres to pH may be reduced, and the acid precursor cannot be fully released in a low pH environment. This highlights the importance of optimizing the ratio of PDEAEMA and PNIPAM in the present invention.

[0127] Comparative Example 6: Preparation method without crosslinking agent

[0128] This comparative example is intended to verify the important role of the cross-linking agent N,N'-methylenebisacrylamide in improving the stability of the polymer carrier, and is compared with Example 2. The method comprises the following steps:

[0129] (1) Preparation of pH and temperature dual-sensitive polymer carriers:

[0130] First, add 200 mL of deionized water to a 500 mL four-necked flask and pass nitrogen for 15 minutes to deoxygenate. Secondly, dissolve 25 parts by weight of PDEAEMA monomer and 10 parts by weight of PNIPAM monomer in 50 mL of anhydrous ethanol and stir evenly. Then, slowly add the monomer solution dropwise to the deionized water with a stirring speed of 300 rpm and a temperature maintained at 25 ° C. Again, add 0.5 parts by weight of ammonium persulfate, heat to 70 ° C, and react for 4 hours under nitrogen protection. Finally, the reaction solution was cooled to room temperature, dialyzed for 48 hours, and freeze-dried to obtain a pH and temperature dual-sensitive polymer carrier.

[0131] Steps (2) to (4) are the same as those in Example 2.

[0132] Furthermore, due to the lack of a crosslinking agent in this comparative example, the network structure of the polymer carrier may not be stable enough and may swell excessively or disintegrate in an acidic environment. This may cause the release rate of the acid precursor to be out of control and fail to achieve a sustained sustained release effect. At the same time, the mechanical strength of the polymer carrier may also be reduced, affecting the stability of the composite microspheres.

[0133] The above six comparative examples fully verify the importance of each key component and process parameter in the present invention. These comparative examples fully demonstrate the superiority of the present invention in terms of multiple response mechanisms, multi-stage release control, stability and safety. This carefully designed controlled release organic solid acid can not only improve the effect and applicability of acidizing treatment, but also reduce environmental risks, providing an innovative technical solution for oil and gas development under complex reservoir conditions.

[0134] In order to comprehensively evaluate the performance of the controlled-release organic solid acid of the present invention, we designed the following test experiments:

[0135] 1. pH responsiveness test

[0136] First, we dispersed the prepared composite microspheres in buffer solutions with different pH values ​​(3, 5, 7, 9). Then, they were incubated at 37°C for 24 hours, and the amount of acid released from the solution was measured every 4 hours. This experiment was designed to evaluate the responsiveness of the composite microspheres to pH changes.

[0137] 2. Temperature responsiveness test

[0138] We dispersed the composite microspheres in phosphate buffer at pH 7 and incubated them at 25°C, 37°C, 60°C, and 80°C. The amount of acid released was measured every 4 hours for 24 hours. The purpose of this experiment was to evaluate the responsiveness of the composite microspheres to temperature changes.

[0139] 3. Sustained release performance test

[0140] The composite microspheres were placed in a solution simulating reservoir conditions (pH 5, 80°C) and the acid release was continuously monitored for 7 days. Samples were taken every 12 hours to measure the cumulative amount of acid released. This experiment was designed to evaluate the long-term sustained-release performance of the composite microspheres.

[0141] 4. Mechanical stability test

[0142] The composite microspheres were placed in an autoclave to simulate reservoir pressure conditions (20 MPa) and maintained at 80°C for 7 days. After that, the samples were taken out to observe the morphology of the microspheres and test their release properties. The purpose of this experiment was to evaluate the stability of the composite microspheres under high temperature and high pressure conditions.

[0143] 5. Core acidification experiment

[0144] Using carbonate cores, the composite microspheres were compared with traditional liquid acid in an acidizing experiment. The experiment was conducted at 80°C and 20MPa, and the permeability change and acid etch morphology of the cores after acidizing were measured. This experiment aims to evaluate the acidizing effect of the composite microspheres under actual reservoir conditions.

[0145] The experimental results are as follows:

[0146] Table 1: pH responsiveness test results (cumulative acid release percentage after 24 hours)

[0147]

[0148]

[0149] Table 2: Temperature responsiveness test results (cumulative acid release percentage after 24 hours, pH 7)

[0150] sample 25℃ 37℃ 60℃ 80℃ Example 1 12.3 18.7 45.6 72.4 Example 2 10.1 15.2 41.8 68.9 Example 3 11.5 16.9 43.7 70.5 Example 4 11.8 17.3 44.2 71.2 Comparative Example 1 19.4 22.5 27.8 31.2 Comparative Example 2 28.7 35.4 59.6 82.3 Comparative Example 3 82.5 85.7 91.2 95.8 Comparative Example 4 13.6 19.2 46.8 73.5 Comparative Example 5 22.3 28.9 65.4 89.7 Comparative Example 6 24.1 29.8 52.7 77.6

[0151] Table 3: Sustained release performance test results (cumulative acid release percentage, pH 5, 80°C)

[0152] sample 1 day 3 days 5 days 7 days Example 1 42.3 68.7 85.2 93.6 Example 2 38.9 64.5 81.8 91.2 Example 3 40.6 66.9 83.7 92.5 Example 4 41.4 67.8 84.5 93.1 Comparative Example 1 45.7 70.2 86.3 94.1 Comparative Example 2 58.9 85.4 95.7 98.9 Comparative Example 3 92.4 98.6 99.5 99.8 Comparative Example 4 43.8 69.5 85.9 94.2 Comparative Example 5 51.2 78.6 91.4 97.3 Comparative Example 6 47.5 73.8 88.9 95.6

[0153] Table 4: Mechanical stability test results (microsphere integrity after 7 days and acid release percentage in 24 hours, pH 5, 80°C, 20MPa)

[0154]

[0155]

[0156] Table 5: Core acidification test results (80℃, 20MPa, 24 hours)

[0157] sample Penetration rate increased by multiples Acid etching channel uniformity (1-10) Example 1 5.8 8 Example 2 6.2 9 Example 3 6 8 Example 4 6.1 9 Comparative Example 3 (Traditional Liquid Acid) 4.2 5

[0158] Results and discussion:

[0159] 1. pH responsiveness: As can be seen from Table 1, Examples 1-4 of the present invention exhibit excellent acid release performance under low pH conditions, while the release amount is significantly reduced under neutral and alkaline conditions. This proves that PDEAEMA plays a good pH response regulating role in the composite microspheres. In contrast, the release performance differences of Comparative Example 1 (no PNIPAM) and Comparative Example 5 (too high PNIPAM ratio) at each pH are small, which illustrates the importance of optimizing the ratio of PDEAEMA and PNIPAM.

[0160] 2. Temperature responsiveness: Table 2 shows that the acid release of Examples 1-4 of the present invention increases significantly with increasing temperature, demonstrating good temperature responsiveness. This is mainly due to the Lower Critical Solution Temperature (LCST) characteristics of PNIPAM. The release difference of Comparative Example 1 (without PNIPAM) at different temperatures is small, further demonstrating the key role of PNIPAM in temperature response.

[0161] 3. Sustained release performance: As can be seen from Table 3, Examples 1-4 of the present invention exhibit excellent sustained release performance, achieving more than 90% cumulative release within 7 days. In contrast, Comparative Example 2 (no nanosilica) and Comparative Example 3 (traditional liquid acid) released too quickly in the early stage and it was difficult to achieve long-term acidification. This highlights the importance of nanosilica in the multi-stage release mechanism.

[0162] 4. Mechanical stability: The results in Table 4 show that Examples 1-4 of the present invention maintain good microsphere integrity and release performance under high temperature and high pressure conditions. The microsphere integrity rate of Comparative Example 6 (without crosslinking agent) is significantly reduced, indicating that the crosslinking agent is crucial to improving the stability of the polymer carrier.

[0163] 5. Core acidizing effect: Table 5 shows that Examples 1-4 of the present invention can more effectively improve the core permeability and form more uniform acid etching channels compared with the traditional liquid acid (Comparative Example 3), which is due to the slow release characteristics and deep acidizing ability of the composite microspheres.

[0164] Unexpected technical effects:

[0165] 1. Synergistic effect: The present invention achieves dual response to the reservoir environment by combining pH-sensitive PDEAEMA and temperature-sensitive PNIPAM. Surprisingly, the combination of these two polymers not only achieves a simple superposition effect, but also produces synergistic effects. Under low pH and high temperature conditions, the swelling of PDEAEMA and the shrinkage of PNIPAM work together to create a unique "squeeze-release" mechanism, further enhancing the release control of the acid.

[0166] 2. Adaptive release dynamics: Experimental results show that the composite microspheres of the present invention can automatically adjust the release rate according to environmental conditions. This adaptability is far beyond expectations, allowing the same preparation to adapt to different reservoir conditions, greatly improving its application range and efficiency.

[0167] 3. Multifunctional role of nano-silicon dioxide: Nano-silicon dioxide was originally introduced to provide physical barriers and delay the release of acid. However, experimental results show that it also plays a role in enhancing the mechanical strength of the composite microspheres. This unexpected enhancement effect allows the composite microspheres to remain stable under high pressure, making it possible for them to be used in deep reservoirs.

[0168] 4. Improvement of acid-etching channels: Core test results show that the composite microspheres of the present invention not only improve permeability, but also significantly improve the uniformity of acid-etching channels. This effect may be due to the uniform distribution and slow release of the composite microspheres, which avoids the wormhole effect in traditional acidizing and provides new possibilities for improving recovery.

[0169] 5. Environmental friendliness: Although the present invention is mainly aimed at improving the acidizing effect, the experimental results unexpectedly show its excellent environmental friendliness. Since the acid is encapsulated in the microspheres, the corrosion to the ground equipment and wellbore is greatly reduced, while the environmental risk of waste acid treatment is reduced.

[0170] Through a series of comprehensive experimental evaluations, the controlled-release organic solid acid of the present invention exhibits excellent pH and temperature responsiveness, sustained release performance, mechanical stability and acidification effect. Its unique multiple response mechanism and multi-stage release control not only achieve the expected technical effects, but also produce a number of unexpected synergistic effects and adaptive characteristics. These innovative characteristics give the present invention significant advantages in acidification treatment under complex reservoir conditions, and provide a new technical path for improving oil and gas recovery. At the same time, its environmentally friendly characteristics also provide possibilities for sustainable oil and gas development. On the whole, Example 2 exhibits the best comprehensive performance and can be regarded as the best implementation scheme of the present invention.

[0171] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a controlled-release organic solid acid, characterized in that: The following steps are involved: (1) Preparing a pH and temperature dual-sensitive polymer carrier; (2) loading the acid precursor onto the polymer carrier; (3) Surface modification of nano-silicon dioxide; (4) The polymer loaded with the acid precursor is mixed with the modified nano-silica, and the composite microspheres are prepared by a spray drying method.

2. The preparation method according to claim 1, characterized in that: The raw material components and their contents used in the method are: 60-80 parts by weight of acid precursor; 15-25 parts by weight of pH sensitive polymer; 5-10 parts by weight of temperature-sensitive polymer; 1-3 parts by weight of a cross-linking agent; 0.5-1.5 parts by weight of surfactant; Initiator 0.1-0.5 parts by weight; 2-5 parts by weight of nano silicon dioxide.

3. The preparation method according to claim 2, characterized in that: The acid precursor is 2-acetoxypropionic acid; the pH sensitive polymer is poly (N,N-dimethylaminoethyl methacrylate) (PDEAEMA); and the temperature sensitive polymer is poly (N-isopropylacrylamide) (PNIPAM).

4. The preparation method according to claim 2, characterized in that: The cross-linking agent is N,N'-methylenebisacrylamide; the surfactant is Tween 80; and the initiator is ammonium persulfate.

5. The preparation method according to claim 1, characterized in that: Step (1) includes the following sub-steps: First, add deionized water into a four-necked flask and pass nitrogen gas to remove oxygen; Secondly, dissolving the pH-sensitive polymer monomer, the temperature-sensitive polymer monomer and the cross-linking agent in anhydrous ethanol and stirring evenly; Then, the monomer solution was slowly added dropwise to deionized water, and the stirring speed and temperature were controlled; Again, the initiator was added, the temperature was raised to 70°C, and the reaction was carried out for 4 hours under nitrogen protection; Finally, the reaction solution was cooled to room temperature, dialyzed for 48 hours, and freeze-dried to obtain a pH and temperature dual-sensitive polymer carrier.

6. The preparation method according to claim 1, characterized in that: Step (2) includes the following sub-steps: First, the acid precursor was dissolved in anhydrous ethanol; Secondly, the polymer carrier is dispersed in deionized water; Then, the acid precursor solution was slowly added dropwise to the polymer carrier dispersion and stirred at room temperature for 2 hours; Finally, the surfactant was added and stirring was continued for 30 minutes.

7. The preparation method according to claim 1, characterized in that: Step (3) includes the following sub-steps: First, nano-silica was dispersed in anhydrous toluene and ultrasonicated for 30 min; Secondly, (3-aminopropyl)triethoxysilane APTES was added and refluxed at 60 °C for 6 hours; Finally, the product was centrifuged, washed with anhydrous ethanol three times, and dried in vacuum at 80 °C for 12 h.

8. The preparation method according to claim 1, characterized in that: The process parameters of spray drying in step (4) are: Feed rate 5-10mL / min, inlet temperature 140-160℃, outlet temperature 60-80℃, atomization pressure 0.2-0.3MPa.

9. The preparation method according to any one of claims 1 to 8, characterized in that: The average particle size of the nano silicon dioxide is 50-100 nm.

10. The preparation method according to any one of claims 1 to 9, characterized in that: The composite microspheres prepared in step (4) were vacuum dried at 60° C. for 24 hours.

Citation Information

Cited By

  • High-temperature acid response type degradable microcapsule acid for acid fracturing and preparation method of high-temperature acid response type degradable microcapsule acid

    CN121674046A